Patterns and predictors of genetic referral among ovarian cancer patients at a National Cancer Institute‐Comprehensive Cancer Center. Issue 2 (24th November 2019) - Mallen, Adrianne R.; Conley, Claire C.; Townsend, Mary K.; Wells, Ali; Boac, Bernadette M.; Todd, Sarah; Gandhi, Anjalika; Kuznicki, Michelle; Augusto, Bianca M.; McIntyre, McKenzie; Fridley, Brooke L.; Tworoger, Shelley S.; et al.
Abstract: Germline mutations (eg, BRCA1 / 2 ) have prognostic and treatment implications for ovarian cancer (OVCA) patients. Thus, national guidelines recommend genetic testing for OVCA patients. The present study examines patterns and predictors of genetics referral in OVCA patients. Electronic medical record data were abstracted retrospectively from 557 OVCA patients treated from 1 January 2001 to 31 December 2015. Logistic regression models identified sociodemographic characteristics, disease/treatment characteristics, family history data, provider characteristics, and survival data that predicted genetics referral. Overall, 27.5% of patients received referral. Eleven variables predicting referral were selected during stepwise regression: younger age, White race, not having private insurance, professional school education, year of OVCA diagnosis, platinum sensitivity, female gynecologic oncologist, chemotherapy administered by a gynecologic oncologist, clinical trial enrollment, longer overall survival, and family history of OVCA. Genetics referral among OVCA patients was similar to rates reported nationwide. Unique predictive factors will contribute to quality improvement and should be validated at a multi‐institutional level to ensure guideline concordant care is provided to all OVCA patients. Future research should identify both patient‐level and provider‐level factors associated with genetics referral. Abstract :